COMPARATIVE STUDY OF JIGSAW AND PROBLEM BASED LEARNING METHODS AMONG FINAL MBBS PART 1 STUDENTS IN COMMUNITY MEDICINE (Asian Journal of Medical Research and Health Sciences, 2026)
Background: In CBME curriculum, more emphasis is done on small group teaching. The self-directed teaching learning methods like jigsaw and problem-based learning methods aid in critical thinking, developing communication and interpersonal skills. However, there is less knowledge about the effectiveness of these methods. Methods:  A quasi- experimental study was conducted among the final MBBS part 1 students in Community Medicine. During the small group teaching sessions, Students were randomly divided into Jigsaw and Problem based groups for learning hypertension. A pre and post-test questionnaire was administered. On Day 2 cross over was done with diabetes topic and perception of students about the methods was obtained. Data was analysed using SPSS software. Results: Jig saw method helped more in enhancing knowledge of participants and this difference was found be statistically highly significant on independent t test (Topic hypertension - t=3.96, p=0.0001 and topic diabetes - T=2.06, p=0.04). On assessing the perception regarding both the methods, students felt jig saw method helps in enhancing communication skills, better retention of the topic and comprehending the topic while Problem based learning helped more in logical thinking, creating intellectual curiosity and in-depth coverage of topic. Conclusions: In our study, Jig saw technique resulted in better academic performance compared to Problem Based learning group. This could be true especially for subjects with well-defined content due to its structured participation.